2013
DOI: 10.1007/s13277-013-1480-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between cytotoxic T lymphocyte antigen-4 +49A/G, −1722T/C, and −1661A/G polymorphisms and cancer risk: a meta-analysis

Abstract: Cytotoxic T lymphocyte antigen-4 (CTLA-4), a key gene that contributes to the susceptibility and clinical course of cancer, is an important down-regulator of T cell activation and proliferation. The +49A/G polymorphism is commonly studied because of its association with cancer risks. However, other polymorphisms, such as -1722T/C and -1661A/G, have not been studied in detail. We performed a meta-analysis using 43 eligible case-control studies with a total of 19,089 patients and 21,388 controls to examine the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 45 publications
3
21
0
1
Order By: Relevance
“…Previous meta-analyses have discussed the association of CTLA-4 polymorphisms with cancer risk [83-85]. To the best of our knowledge, we are the first to perform such a comprehensive meta-analysis of the common functional polymorphisms of the CTLA-4 gene comprising all the published and well-defined case-control studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analyses have discussed the association of CTLA-4 polymorphisms with cancer risk [83-85]. To the best of our knowledge, we are the first to perform such a comprehensive meta-analysis of the common functional polymorphisms of the CTLA-4 gene comprising all the published and well-defined case-control studies.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown the association of CTLA-4 polymorphisms with allograft rejection, endstage renal disease, delayed graft function and infection after renal transplantation [29][30][31][32] , and the expression pattern of the protein encoded by CTLA4 was found to be altered by the polymorphisms rs4553808 (-1661A/G) in the CTLA4 gene promoter [33] . It is reported that a carry of G allele variation will increase CTLA4 mRNA level and expression, thereby promoting consensus sequence in the regulatory region of the CTLA4 promoter in humans [26,34] . The result of our study revealed that polymorphism of rs4553808 (-1661A/G) in CTLA4 gene promoter may influence TAC dose requirement.…”
Section: Discussionmentioning
confidence: 99%
“…It causes a 17Thr to 17Ala substitution in the leading peptide of CTLA-4 receptor. Its role in increasing cancer susceptibility is well known in various populations across the world, especially Asians (Geng et al, 2013). The effect of SNPs on cancer susceptibility differs in different ethnic populations and there is no data till date with respect to the effect of this SNP on breast cancer susceptibility in our North Indian population.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand it is known to increase the susceptibility of various autoimmune diseases and on the other hand it is also known to be associated with susceptibility and aggressiveness of various cancers (Ghaderi et al, 2011;Geng et al, 2013). Its role in skin cancer is well documented and we now even have a drug (Ipilimumab) against this important molecular target (Blank, 2014).…”
Section: Introductionmentioning
confidence: 99%